UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPS MELALUI PENGGUNAAN MEDIA PEMBELAJARAN MEDIA ASLI REMPAH – REMPAH (MAAR) - Wibawanto, Prasnowo (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2024)
This research is a Classroom Action Research (CAR). The subjects of the research were 32 students of class VIII A of SMP Negeri 2 Girimarto. Data collection techniques used written test methods, observation, documentation. The research procedure was carried out through two cycles and each cycle consisted of planning, implementation, observation and reflection. The results of the study showed (1) an increase in learning outcomes, this can be seen from: (a) an increase in the completeness of learning of participants when compared between the pre-cycle, namely 12 students (37.59%) at the end of cycle 2 to 32 students (100%) so that it has reached the level of completeness as determined, namely 100%; (b) there was an increase in the average value when compared between the pre-cycle 68.75 at the end of cycle 2 to 91.25 so that there was an increase of 15.62. (2) there was an increase in learning activity when compared between the pre-cycle cycle, namely the average value of 2.94 (moderate) increased at the end of cycle 2 to 4.13 (good) so that there was an increase of 1.19.